Detection of rotational errors in single‐isocenter multiple‐target radiosurgery: Is a routine off‐axis Winston–Lutz test necessary?. Issue 9 (17th June 2022) - Pudsey, Lauren M. M.; Biasi, Giordano; Ralston, Anna; Rosenfeld, Anatoly; Poder, Joel
Abstract: Purpose: Recently the use of linear accelerator (linac)‐based stereotactic radiosurgery (SRS) has increased, including single‐isocenter multiple‐target SRS. The workload of medical physicists has grown as a result and so has the necessity of maximizing the efficiency of quality assurance (QA). This study aimed to determine if measurement‐based patient‐specific QA with a high‐spatial‐resolution dosimeter is sensitive to rotational errors, potentially reducing the need for routine off‐axis Winston–Lutz (WL) testing. Methods: The impact of rotational errors along gantry, couch, and collimator axes on dose coverage of the gross tumor volume (GTV) and planning target volume (PTV) was determined with a 1‐mm GTV/PTV expansion margin. Two techniques, the off‐axis WL test using the StereoPHAN MultiMet‐WL Cube (Sun Nuclear Corporation, Melbourne, Florida, USA) and patient‐specific QA using the SRS MapCHECK (Sun Nuclear Corporation, Melbourne, Florida, USA), were assessed on their ability to detect introduced errors before target coverage was compromised. These findings were also considered in the context of routine machine QA of rotational axis calibrations. Results: Rotational errors significantly impacted PTV dose coverage, especially in the couch angle. GTV dose coverage remained unaffected except for with large couch angle errors (≥1.5°). The off‐axis WL test was shown to be sensitive to rotational errors with results consistently exceeding tolerance levels when or before coverage fell below departmentally accepted limits. Although patient‐specific QA using the SRS MapCHECK was previously validated for SRS, this study showed inconsistency in detection of rotational errors. Conclusions: It is recommended that off‐axis WL testing be conducted regularly to supplement routine monthly machine QA, as it is sensitive to errors that patient‐specific QA may not detect. This frequency should be determined by individual departments, with consideration of GTV–PTV margins used, limitations on target off‐axis distances, and routine mechanical QA results for particular linacs.